Assessment of IrO2-Ta2O5|Ti electrodes for the electrokinetic treatment of hydrocarbon-contaminated soil using different electrode arrays. (1st August 2016) - Cuevas, O.; Herrada, R.A.; Corona, J.L.; Olvera, M.G.; Sepúlveda-Guzmán, S.; Sirés, I.; Bustos, E.
Graphical abstract: Highlights: 1D and 2D configurations have been tested by employing IrO2 -Ta2 O5 |Ti. Radial 2D array showed 58% HC removal near the anode applying 30 V. Applying 2.4 A cm −1 after 24 h of treatment was obtained the best removal. IrO2 -Ta2 O5 |Ti anodes contributed to obtain the major removal efficiency. Morphology of the anodes has been analyzed by SEM-EDX. Abstract: In recent years, physicochemical processes such as electrokinetic treatment (EKT) have gained acceptance as suitable alternatives to restore hydrocarbon (HC)-contaminated sites. EKT entails relatively short times and high removal efficiencies, usually being applied in heterogeneous soils with low permeability. In this work, 1D (one-dimensional) and 2D (two-dimensional) configurations have been tested employing Ti cathodes and anodes, as well as purpose-made IrO2 -Ta2 O5 |Ti as dimensionally-stable anodes (DSA ® ). After EKT and from GC-MS analysis of fat and oil content, it has been found that the radial 2D array with one central Ti cathode and six IrO2 -Ta2 O5 |Ti anodes performed the best removal efficiency of hydrocarbons. The removal efficiencies of using modified electrodes with a configuration of circular 2D electrodes had double the removal efficiency (58%) over the use of a configuration of face-to- face 1D array (21%) with the IrO2 -Ta2 O5 |Ti anode and Ti cathode. Finally, the superficial morphology of IrO2 -Ta2 O5 |Ti anode and Ti cathode were not affected by EKT, which was demonstrated with the same appearance before and after EKT in the micrographs obtained by SEM.